Investigation of fatigue and mechanical properties of the pipe grade poly(vinyl chloride) using recycled scraps - J-M. Lee; J-S. Moon; H. Lee; B-H. Choi (eXPRESS Polymer Letters, 2015)
In this paper, the effect of using pre-consumer PVC scraps on static and long-term mechanical properties is studied. The degradation characteristics of mixing virgin PVC with crushed pre-consumer and PVC pipe scraps are analyzed using various tools including Gel Permeation Chromatography (GPC), Thermogravimetric Analysis (TGA), X-ray fluorescence (XRF) and Fourier Transform Infrared (FTIR) spectroscopy. The variation of static mechanical properties as a function of adding pre-consumer PVC pipe scraps is investigated using the degradation analyses of recycled PVC scraps. In addition, fatigue tests are executed to evaluate the long-term durability of blending virgin PVC and recycled PVC scraps, and the fracture surface is investigated in detail to reveal the variation of the fracture mechanisms.